PENGARUH KUALITAS PELAYANAN PERPUSTAKAAN TERHADAP MINAT BACA SISWA DI SDN 8 PULAU RIMAU KABUPATEN BANYU ASIN PROVINSI SUMATERA SELATAN - Puryanto; Fatma, Riska (Jurnal Al- Ma'arif : Ilmu Perpustakaan dan Informasi Islam, 2024)
"This research aims to find out whether there is an influence of the quality of library services on students' reading interest at SDN 8 Pulau Rimau, Banyuasin Regency, South Sumatra Province. The approach in this research is quantitative descriptive. The sample in this research was classes V and VI, totaling 50 students. The data collection technique in this research is a questionnaire. The results of the research show that there is a significant influence between the quality of library services and students' reading interest. This indicates that work discipline positively influences employee performance because the t-table value and significance level are < (0.05), indicating a positive influence. Based on the coefficient of determination test results, R square has a value of 0.617 or 61.7%. This figure illustrates the extent of the variable influence of Library Service Quality on students' reading interest, while the remaining 39.3% is influenced by other variables outside this regression equation or variables that were not studied."